Pengaruh Digital Strategy, Accounting information Quality terhadap Digitalization Adoption (Studi Empiris Pada Pelaku Usaha Mikro Kota Lubuk Linggau) - Bella Nur Anggraini; Eri Triharyati; Dian Wulan Sari; Indrawati Mara Kesuma (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to find out and analyze the impact of the unfluence of Digital Strategy, Accounting Information Quality on Digitalization Adoption on Micro Enterprises in Lubuklinggau City. The population in the study is 29,536 micro businesses. To determine the sample in this study, the calculation of the Slovin Formula was used to that it became 100 samples in the micro business of Lubuklinggau City. The method used in this study is the Quantitative Research Method. The data in this study was collected using a questionnaire that had been distributed to micro businesses in Lubuklinggau City and analyzed the data using SPSS Statistics 27. The results in this study are that Digital Strategy has significant effect on Digitalization Adoption, Accounting Information Quality has a significant effect on Digitalization Adoption, dan the Regression Model Detects the influence of Digital Strategy, Accounting Information Quality on Digitalization Adoption.